The Yield of Red Podded Yardlong Bean Genotypes (Vigna unguiculata L.) under Shading - Zulfaa, Latifah; Anwar, Syaiful; Kusmiyati, Florentina; Putra, Fajrin Pramana (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2024)
Yardlong bean is a plant with high nutritional value, but it is not considered a main crop. Land extensification with agroforestry is needed to overcome land limitations and maximize yardlong bean production. The research aims to produce yardlong bean varieties that adapt to shading conditions in agroforestry systems. The research was conducted from October 2023 to February 2024. The research design used a Split Plot based on a Completely Randomized Design (CRD). The main plot was shading with two levels, no shading (N0), and 50% paranet shading (N1). The subplots were parental FG genotypes of the F8 generation, namely FS 7-1-8, FS 10-1-8, FS 10-3-8, FS 14-2-8, and FS 8-2-8. Observation parameters included the time of 50% flowering, fresh harvest age, leaf stomata count, leaf chlorophyll and carotenoid content, number of fresh pods per plant, fresh pod weight per plant, and productivity. Data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level and Tukey’s HSD test at 5%. The results showed that the genotype factor significantly affected the time of 50% flowering. Shading treatment significantly affected the number of leaf stomata. Shading and yardlong bean genotypes did not significantly differ in leaf chlorophyll and carotenoid content, fresh harvest age, the number of fresh pods per plant, fresh pod weight per plant, and productivity. The F8 generation yardlong bean plants showed tolerance to shading as they could maintain growth and yield. The FS 10-1-8 genotype has the fastest flowering speed compared to the FG parent.